Severe unconjugated hyperbilirubinaemia with infradiaphragmatic total anomalous pulmonary venous connection. - Burch, M (1993)
An 8 day old girl with infradiaphragmatic total anomalous pulmonary venous connection presented with severe unconjugated hyperbilirubinaemia; exchange transfusion resulted in haemodynamic deterioration. Hyperbilirubinaemia is a rare complication of this condition, however exchange transfusion should be avoided. The diagnosis can be made on the neonatal unit by ultrasound demonstration of dilated hepatic portal veins.